2011
DOI: 10.1037/a0025157
|View full text |Cite
|
Sign up to set email alerts
|

Automatic cognitions and teen dating violence.

Abstract: Objective: The present research examined whether the level of aggression in automatic cognitions was positively associated with teen dating violence after accounting for more consciously controlled, self-reported attitudes about dating violence. Method: At baseline, 95 teens who had been remanded to the juvenile court system because of antisocial behavior completed a word-completion task designed to measure the level of aggression in their automatic cognitions. Teens also completed questionnaire measures of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…To our knowledge, there are no studies that have tested this mediational model with dating violence. Nevertheless, the study by Jouriles, Grych, Rosenfield, McDonald, and Dodson (2011) found that, among adolescents, the level of aggression in automatic cognitions was concurrently and prospectively related to dating violence perpetration after controlling for self-reported attitudes about dating violence, which indicates that different levels of cognitive processes are important to explaining the perpetration of dating violence.…”
Section: Sip As a Mediator Between Acceptance Of Violence Beliefs Andmentioning
confidence: 93%
“…To our knowledge, there are no studies that have tested this mediational model with dating violence. Nevertheless, the study by Jouriles, Grych, Rosenfield, McDonald, and Dodson (2011) found that, among adolescents, the level of aggression in automatic cognitions was concurrently and prospectively related to dating violence perpetration after controlling for self-reported attitudes about dating violence, which indicates that different levels of cognitive processes are important to explaining the perpetration of dating violence.…”
Section: Sip As a Mediator Between Acceptance Of Violence Beliefs Andmentioning
confidence: 93%
“…Outcome expectancies also predict dating violence perpetration in short-term longitudinal studies (Jouriles et al 2011). However, some researchers have failed to find a relation between teens' explicit beliefs about dating violence and perpetration of relationship violence (Wolfe et al 2004).…”
Section: Social Cognitive Processes: Explicit Beliefsmentioning
confidence: 98%
“…A single study to date has examined implicit knowledge structures and their relation to dating violence (Jouriles et al 2011). In a sample of teens recruited through the juvenile court system, implicit knowledge structures were assessed using a method designed to assess the accessibility of aggressive thoughts (Anderson et al 2003).…”
Section: Extending Theory: Implicit Knowledge Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, exposure to neighborhood violence may positively impact children’s beliefs about the justifiability of aggression via normative associations (Fosco, Grych, & DeBoard, 2007). Violent individuals have more positive attitudes toward dating aggression and may use these beliefs to justify their violent behavior (Jouriles, Grych, Rosenfield, McDonald, & Dodson, 2011). Among child-mother dyads recruited from a domestic violence shelter who recently experienced severe IPV, children’s beliefs about the justifiability of aggression were positively associated with children’s self-reports of more externalizing problems (i.e., disruptive behavior) six months later (Jouriles, Vu, McDonald, & Rosenfield, 2014).…”
Section: Introductionmentioning
confidence: 99%